The mirage of a triune rainbow - E.M. Conradie (Acta Theologica)
This contribution explores the state of the debate on the triune God in theological discourse in South Africa. It assesses the direction in which this debate is going in conversation with Prof. Rian Venter, one of the senior scholars contributing to this debate. It is written in the form of an “academic letter” that assumes the requisite scholarship, but deliberately engages in a conversation that is appropriate to the exploratory approach that is adopted and honours the correspondent upon his retirement. In a somewhat playful manner, a colourcoding for such discourse is proposed, identifying white, dark purple, light purple, green, brown, black, and grey perspectives on the Trinity. On this basis, the thesis is developed that discourse on the triune God takes place in self-isolating silos, so that conversation between these silos becomes difficult. In theory, a creative tension between these discourses can yield a rainbow alliance. It is, however, argued that no such attractive South African “rainbow” is emerging in this regard. South African debates may well serve as a barometer, or better, a thermometer to gauge the health of wider ecumenical discourse on the Trinity.